Trends in antibiotic utilization for patients hospitalized with COVID-19 with and without signs of sepsis - Claire N. Shappell; Michael Klompas; Christina Chan; Tom Chen; Chanu Rhee (Cambridge University Press, 2024)
Abstract Objective: To assess trends in antibiotic prescribing for patients hospitalized with COVID-19 with and without sepsis. Design: Retrospective cohort study using electronic health record (EHR) data. Setting: Five hospitals in eastern Massachusetts. Patients: Adults (≥18 years) hospitalized with community-onset SARS-CoV-2 infections between March 2020 and November 2022. Methods: We assessed quarterly trends in the use of prolonged initial antibiotic therapy (≥4 antibiotic days within one week of admission, including discharge antibiotics) amongst COVID-19 patients with and without sepsis, defined using clinical signs of organ dysfunction before hospital day 3. Poisson regression models were used to adjust for baseline characteristics and severity of illness. Results: Of 431,017 hospitalizations in the study period, 21,563 (5.0%) had community-onset COVID-19. 4,769/21,563 (20.5%) presented with sepsis. Prolonged antibiotics were prescribed in 2,323/4,769 (48.7%) COVID-19 patients with sepsis and 2,866/16,794 (17.1%) without sepsis despite low rates of positive bacterial cultures on admission (15.0% vs 6.3%, respectively). Quarterly rates of prolonged antibiotics declined between the first and second pandemic quarters for both sepsis (66.8% to 43.9%) and no-sepsis (31.8% to 24.4%) groups. However, there was no significant change thereafter through November 2022 in either group (quarterly aORs 1.02, 95% CI 0.99-1.05 and 1.01, 95% CI 0.99-1.03, respectively). Conclusions: Prolonged antibiotics were common in hospitalized COVID-19 patients with and without sepsis during the first 33 months of the pandemic despite low rates of proven bacterial infection. Decreases in antibiotic utilization occurred primarily between the first and second pandemic quarter with no further reduction thereafter.